Roeky Mountain Spotted Fever Vaccine: A Regional Need - Walker, David H.; Montenegro, Mario R. [UNESP]; Hegarty, Barbara C.; Tringali, Giuseppe R. (Southern Medical Association, 1984)
Because the killed Rickettsia vaccines have failed to provide protection against Rocky Mountain spotted fever, we approached the problem of protective immunity to Rickettsia rickettsii with a closely related, live, less pathogenic spotted fever Rickettsia. Guinea pigs vaccinated with R conorii produced antibodies to spotted fever group rickettsiae and did not have fever or other signs of illness after challenge with R rickettsii. A vaccine against Rocky Mountain spotted fever would be useful in some medical practices in the southeastern United States because of the life-threatening nature of the disease, including the possibility of a fulminant course and the frequent difficulty in diagnosis. Further studies should be pursued toward the goal of developing an effective vaccine against Rocky Mountain spotted fever. © 1984 Southern Medical Association.